Community radio regulation and its challenges in Ghana. (1st September 2012) - Ufuoma, Akpojivi
The emergence of community radio in Ghana's media sphere has changed the political economy of communications in Ghana. The participatory platform of the medium has led to citizens' empowerment and facilitated the political, economic and social development of this new democracy. Marginalized communities are now able to question policies. The views expressed during these participatory programmes like live phone-in have helped to promote accountability and transparency within government circles and the corporate world. However, concerns have been raised over the serious allegations and mischievous remarks made on community radio stations and how they can be regulated. This article shall argue that the complex and intricate nature of the regulatory mechanism and the conceptualization of community radio have made it difficult for the regulatory body, National Media Commission (NMC) to regulate the community radio. Seeing that Ghana is a multi-ethnic state, her democracy may be endangered if the content from community radio stations which could heat up the polity is not regulated.